Waardenburg syndrome: case series - Sachdeva, Sheenu; Jayakumar, Varunkumar; Jaiswal, Shubhlaxmi Atmaram (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Waardenburg syndrome is a rare genetic disorder of neural crest cell development with incidence of 1:42000 to 1:50,000. The syndrome is not completely expressed and hence adds to its hetergenecity with symptoms varying from one type of syndrome to another and from one patient to another. Unilateral heterochromia that manifests in some people is associated with Waardenburg syndrome and Parry-Romberg syndrome. This is a case series of four cases with features of Waardenburg syndrome with variable presentations and familial inheritance.